Serum Creatinine Levels and Nephrocheck® Values With and Without Correction for Urine Dilution-A Multicenter Observational Study - Hahn, Robert G.; Yanase, Fumitaka; Zdolsek, Joachim H.; Tosif, Shervin H.; Bellomo, Rinaldo; Weinberg, Laurence (Frontiers in Medicine, 2022)
Background. The Nephrocheck® test is a single-use cartridge designed to measure the concentrations of two novel cell-cycle arrest biomarkers of acute kidney injury, namely tissue inhibitor of metalloproteinase 2 (TIMP-2) and insulin-like growth factor binding protein 7 (IGFBP7). Correlations of serum creatine values and TIMP-2 and IGFBP7 with and without correction for urine dilution have not been previously undertaken in patients undergoing major abdominal surgery. We hypothesized that the Nephrocheck® values would be significantly different with and without correction for urine dilution in patients with elevated creatinine values post major abdominal surgery. Methods. We performed a post hoc analysis of serum and urine specimens sampled preoperatively and postoperatively in 72 patients undergoing major abdominal surgery. Thirty samples were measured from patients with the greatest decrease and the greatest increase in postoperative serum creatinine values. Urine was analysed with the Nephrocheck to predict the risk of acute kidney injury (AKIRisk™). We then examined the relationship between serum creatinine and the urinary excretion of TIMP-2 and IGFBP7 as measured by the Nephrocheck test. The AKIRisk between the groups with and without correction for urine dilution was assessed. Results. The median perioperative change in serum creatinine in the two groups was -19% and +57%, respectively. The uncorrected median baseline AKIRisk decreased from 0.70 (25th–75th percentiles, 0.09–1.98) in the first group and rose from 0.57 (0.22–1.53) to 0.85 (0.67–2.20) in the second group. However, when corrected for the squared urine dilution, the AKIRisk™ in patients with postoperative increases in serum creatinine was not indicative of kidney injury; the corrected AKIRisk was 8.0 (3.2–11.7) µg2/mmol2 before surgery versus 6.9 (5.3–11.0) µg2/mmol2 after the surgery (P = 0.69). Conclusion. In the setting of major abdominal surgery, after correction of TIMP-2 and IGFBP7 for urine dilution, the Nephrocheck AKIRisk scores were significantly different from the uncorrected values. These finding imply that the AKIRisk index is a function of urine flow in addition to an increased release of the biomarkers.